Modelling Fuel Cut Off Controller on Cng Engines Using Fuzzy Logic: A Prototype - Suroto Munahar; Muji Setiyo; Dori Yuvenda; Madihah Mohd Saudi; Azuan Ahmad (INSIGHT - Indonesian Society for Knowledge and Human Development, 2024)
Indexed by Scopus/ERA